CO2 Hydrogenation Mechanism on Graphene-supported Subnanometer Ni7 Cluster - Saputro, Adhitya Gandaryus; Pradana, Mochammad Rizky; Maulana, Arifin Luthfi; Agusta, Mohammad Kemal; Dipojono, Hermawan Kresno (Journal of Research and Development on Nanotechnology, 2021)
We study the mechanism of carbon dioxide (CO2) hydrogenation to carbon monoxide (CO) and formic acid (HCOOH) on a graphene-supported subnanometer Ni7 cluster by means of density functional theory calculations. We find that this system has similar activation energies for the first CO2 hydrogenation step for the formate and RWGS pathways. However, the second hydrogenation step for these pathways has very distinct profiles. The HCOOH formation on the formate pathway has very large activation energy, while the CO formation on the RWGS pathway has negligible activation energy. We conclude that the CO2 hydrogenation process on this system is more selective towards the RWGS pathway to produce CO.